'You never told me I would turn into a gambler': a first person account of dopamine agonist – induced gambling addiction in a patient with restless legs syndrome. (24th August 2011) - Jones, Henrietta Bowden; George, Sanju
Abstract : Dopaminergic agents are commonly used and effective treatments for restless legs syndrome (RLS), a disabling sensorimotor disorder. Less known are some of the potentially disabling side effects of these treatments, particularly iatrogenic gambling addiction, as is described here. Here the authors present a 62-year-old man, with a 20–year history of RLS, who developed gambling addiction while on dopaminergic treatment. He was not forewarned of this side effect, nor was he ever screened for gambling behaviours prior to or during treatment. Eight months after discontinuation of dopaminergic treatment and after 10 sessions of cognitive–behavioural therapy for gambling addiction, his gambling behaviours have partially resolved. To our knowledge, this is the first ever first person account of this condition. To prevent the devastating consequences of gambling addiction or to minimise its impact by early intervention, the authors call for clinicians involved in treatment of RLS to follow these simple measures: screen patients for gambling behaviours prior to the onset and during dopaminergic treatment; forewarn patients of this potential side effect; and if patients screen positive, refer them to specialist gambling treatment services, in addition to making necessary changes to their medication regime.